DIDACTIC MODELS OF LABOR EDUCATION IN THE PROCESS OF ACQUAINTING MIDDLE-GROUP CHILDREN WITH NATURE IN PRESCHOOL EDUCATION ORGANIZATIONS (Ideal Journal of Multidisciplinary Research, 2026)
This article explores the theoretical and practical aspects of organizing labor activities for children aged 4–5 years within the framework of nature acquaintance sessions. The role of labor education in the intellectual and physical development of the child is substantiated from a psychophysiological perspective. Furthermore, the article elucidates the implementation mechanisms of modern technologies, such as the "Project Method," "Interactive Observation," and "Ecological Modeling," into the activities of middle-group pupils.
Keywords: Integrative approach, sensory development, ecological didactics, middle group, labor algorithm, nature corner, psychopedagogical correction.